2021
DOI: 10.3389/fmed.2021.728693
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Sickle Cell Disease: Plasma Concentration, Blood Cell Types Origin Distribution and Biological Properties

Abstract: Prototype of monogenic disorder, sickle cell disease (SCD) is caused by a unique single mutation in the β-globin gene, leading to the production of the abnormal hemoglobin S (HbS). HbS polymerization in deoxygenated condition induces the sickling of red blood cells (RBCs), which become less deformable and more fragile, and thus prone to lysis. In addition to anemia, SCD patients may exhibit a plethora of clinical manifestations ranging from acute complications such as the frequent and debilitating painful vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…Indeed, similar to other tests based on blood samples, EVs quantification and characterization is less invasive than many other techniques used to directly assess biological states. Therefore, EVs could be biomarkers with a clinical utility in determining risk in several diseases, including SCD [ 9 ]. Originally described as cell dust [ 10 ], it has been shown that EVs play a role in cell-to-cell communication at both paracrine and systemic levels [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, similar to other tests based on blood samples, EVs quantification and characterization is less invasive than many other techniques used to directly assess biological states. Therefore, EVs could be biomarkers with a clinical utility in determining risk in several diseases, including SCD [ 9 ]. Originally described as cell dust [ 10 ], it has been shown that EVs play a role in cell-to-cell communication at both paracrine and systemic levels [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of different kinds of EVs in the pathogenesis of SCD is increasingly becoming appreciated (as reviewed by [36]). Several different roles have been documented for medium-sized EVs (microparticles) derived from red cells, monocytes, platelets, and endothelial cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…Sickle cell disease (SCD) is caused by a hemoglobin mutation, leading to the deformation of red blood cells and chronic complications including anemia, hypercoagulation, and inflammation. 55 In patients with SCD, vaso-occlusive crises can lead to pathologies such as lung injury. 56 Lung injuries in a humanized mouse model can be mediated via PEV-derived IL-1β and caspase-1, which activates platelets, neutrophils, and vascular cells, thus resulting in plateletneutrophil aggregates large enough to block pulmonary arterioles.…”
Section: Blood Cell Disordersmentioning
confidence: 99%
“…Sickle cell disease (SCD) is caused by a hemoglobin mutation, leading to the deformation of red blood cells and chronic complications including anemia, hypercoagulation, and inflammation 55 . In patients with SCD, vaso‐occlusive crises can lead to pathologies such as lung injury 56 .…”
Section: Megakaryocyte and Platelet Evs In The Pathogenesis Of Diseasementioning
confidence: 99%